Initial Spacing and Growth of Pinus caribaea - Kaul, R. N.; Sharma, K. K. (Indian Forester, 1982)
The paper presents the results of spacing trials on Pinus caribaea var. bahomensis. The growth data at 8-9 years of age indicate that P. coribaea does possess a potential of high yields and where tree size is not of mach importance as in the case of pulpwood, it should be planted dense i.e. at a spacing of 2 m2. However, from the observation of the plots indicate unhealthy (lanky trees) under closer spacings. It is, therefore, likely that in the years to come the growth in plots with closer spacing may fa1l whereas under wider spacing the crop may continue to be healthier. It is probable that the best spacing might lie between 2 m2 and 2.5 m2. This could only be concluded after the experiment progresses for some more years.